Utilizing IT to Enhance Knowledge Sharing for School Educators in Developing Countries. Issue 1 (5th December 2017) - Kalema, Billy M.M.; Motsi, Lovemore; Motjolopane, Ignitia M.
Abstract: Knowledge has been considered a critical factor for any organization's survival however its retention and utilization has remained a challenge to many organizations in developing countries education institutions inclusive. These challenges are mostly attributed to the fact that knowledgeable employees often leave organizations before they could share their valuable knowledge and expertise. In schools of developing countries in particular, educators struggle for subsistence and many leave to seek for greener pastures. Such exodus of educators has led to knowledge loss and has widened the knowledge gap between the schools for the rich and those for the poor. This has been worse especially in the most challenging subjects like Science and Mathematics. Closing this gap, schools need to depend on the knowledge of other experienced educators that are still in the Education system in order to enhance the capabilities of those that are inexperienced. For this reason, leveraging Information Technology (IT) to facilitate the sharing of knowledge, communicate ideas, exchange views and information between educators is paramount. There is a need for schools in developing countries' to have guidelines of how IT could be utilized for knowledge sharing. The major objective of this paper is therefore to report on the utilization of IT to enhance Knowledge Sharing (KS) among educators in developing countries taking a case of South Africa. The Social Exchange Theory (SET), Theory of Reasoned Action (TRA) and The Unified Theory of Acceptance and Use of Technology (UTAUT) were used to design a conceptual framework for the study. Data was collected from secondary schools' educators in Tshwane South district of South Africa and was analyzed quantitatively. The results indicated that, knower's attitude is a high significant contributing factor whereas dependence of the knower is the least and insignificant in the utilization of IT to enhance knowledge sharing. Practically, this study could be leveraged by schools and governments to entrench tacit knowledge and to address the brain drainage associated with the continuous exodus of the skilled and experienced educators. Further still, the designed framework could be used by Information Systems scholars to extend research of knowledge sharing and management.